Strategi Pelestarian Bangunan-Bangunan Lama pada Koridor Heerenstraat Probolinggo - Sayyidah Rafi Dianya Shabri; Bambang Soemardiono; Sarah Cahyadini (Universitas Sebelas Maret Surakarta, 2024)
One of the Dutch legacies in Probolinggo is the Heerenstraat Corridor. Despite having high historical value, the buildings along this corridor face major challenges in terms of preservation, mainly due to changes that change the characteristics of the corridor as a Dutch heritage. Therefore, this study aims to develop an effective preservation strategy for old buildings on Jalan Suroyo or the Heerenstraat corridor. The research method is to analyze the condition of the building, identify preservation constraints, and formulate a preservation strategy to ensure the sustainability of the buildings and corridor. This study highlights the lack of awareness, changes in building functions, and the absence of detailed regulations that cause problems in building preservation in Heerenstraat Probolinggo. Physical protection is needed to maintain and restore buildings. Various preservation approaches such as preservation, conservation, reconstruction, and adaptation are proposed as steps to preserve old buildings in the Heerenstraat corridor.